2020
DOI: 10.1007/s10973-020-09375-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermal analysis of W-free Co–(Ni)–Al–Mo–Nb superalloys

Abstract: In this investigation, the thermal analysis of W-free cobalt-based superalloys based on Co–Al–Mo–Nb and Co–Ni–Al–Mo–Nb systems was performed. The analysis was performed at different stages of heat treatment process. The differential thermal analysis (DTA) was utilized for the determination of characteristic temperatures related to microstructural changes. First of all, the DTA analysis was carried out for discussing as-cast alloys in the temperature range of 40–1500 °C. The results showed thermal effects conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
(22 reference statements)
1
5
0
Order By: Relevance
“…Makineni et al [15] reported on the formation of intermetallic compounds Co 3 (Mo,Nb) with the D019 structure and CoAl with the B2 structure in the Co-10 at.% Al-5 at.% Mo-2 at.% Nb alloy after annealing for 35 h at 800 • C. These phases, as suggested, were formed due to the decomposition of the ordered γ -phase (Co 3 (Al,Nb,Mo)). On the other hand, in the same alloy Co-10Al-2Nb-5Mo, the presence of the Co 2 Nb Laves phase was reported by Damian Migas et al [16] (Table 2). In order to accurately establish the crystal structure of intermetallic phases in the studied quaternary alloys of the Co-Al-Nb-Mo system, first, we conducted a study of binary (Co-10Al) and ternary alloys (Co-10Al-X%Nb and Co-10Al-Y%Mo).…”
Section: Resultssupporting
confidence: 75%
“…Makineni et al [15] reported on the formation of intermetallic compounds Co 3 (Mo,Nb) with the D019 structure and CoAl with the B2 structure in the Co-10 at.% Al-5 at.% Mo-2 at.% Nb alloy after annealing for 35 h at 800 • C. These phases, as suggested, were formed due to the decomposition of the ordered γ -phase (Co 3 (Al,Nb,Mo)). On the other hand, in the same alloy Co-10Al-2Nb-5Mo, the presence of the Co 2 Nb Laves phase was reported by Damian Migas et al [16] (Table 2). In order to accurately establish the crystal structure of intermetallic phases in the studied quaternary alloys of the Co-Al-Nb-Mo system, first, we conducted a study of binary (Co-10Al) and ternary alloys (Co-10Al-X%Nb and Co-10Al-Y%Mo).…”
Section: Resultssupporting
confidence: 75%
“…[20][21][22][23][24][25][26] Typically, for this type of alloys, treatment consisting in homogenization and supersaturation or only supersaturation at a temperature range of 1250-1300 °C for up to 24 hours with cooling in water, followed by late supersaturation in the range of the solvus temperature of the L1 2 phase, i.e., 900-1000 °C. [27][28][29] In the study, we analyze qualitatively and quantitatively the c-c 0 type Co-based alloys. For this purpose, different ternary, quaternary and quinary alloys were prepared, including two c 0 -Co 3 (Al, W) forming alloys and two W-free ones.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ] An appropriate content (about 2–5 at%) of Mo to stabilize γ' precipitates in Co‐based superalloys is also a favorable alloying method. [ 15 ] The addition of Ti can promote the formation of γ'‐(Co, Ni) 3 (Al, Ti) precipitates and significantly increase the volume fraction of γʹ. Furthermore, Cr can improve the oxidation resistance of Co‐based superalloy and help to improve the toughness of materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, it will inversely decrease the oxidation resistance due to the evaporation of Mo‐containing oxide at high temperatures. [ 15,23 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation